Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques